Teaching International Human Rights Law In Vietnam: How To Make This Subject Attractive To University Students - Ha, Nguyen Thi (UI Scholars Hub, 2022)
Human Rights is one of the achievements of the historical development of mankind, characteristic of civilized society, and also one of the basic and important legal values of humanity. In the context of international integration of education in general and higher education in particular, the teaching of human rights, first of all, international human rights law is important for undergraduate students, especially in helping them to identify and understand the responsibility to make human rights become a reality in society. Human rights teaching aims to help learners orient and understand noble human values, common voices, common goals, and common means of all humanity to safeguard and advance human dignity and happiness. In the face of globalization, human rights education has been attracting the attention of domestic and foreign scientists and many international organizations. In Vietnam, teaching international human rights law has been implemented at universities, first of all, law universities. This article attempts to give an overview of the teaching of International Human Rights Law in Vietnam today by exploring the reasons why students are not amenable and interested in the subject yet. In the whole article, the author explores and surveys the curriculum of international human rights law in law universities in Vietnam to make initial but overall judgments and assessments about the teaching situation of international human rights law in Vietnam. Based on analysis and evaluation of the content of the curricula, learning materials, and especially teaching and learning methods, the article proposes solutions to enhance the attractiveness and attract the interest of students to the subject. From solutions on compiling the content of textbooks and documents to solutions on active teaching methods as well as the application of information technology and social networks and so on, will contribute to increasing the interest and attraction of students to the subject. The article concludes that although progress has been made in the past two decades, the teaching of international human rights law in Vietnam has not caught up with the general development trend around the globe nor met the needs of the demand for human rights education in the nation, notably this subject has not yet brought fascination to students. The main obstacles in teaching human rights in Vietnam today are related to issues such as it is not a compulsory subject in the curriculum framework of the government, the teaching content is still limited; lecturers are not specialized and limited in foreign languages; the lack of reference materials as well as outdated teaching methods.